2019
DOI: 10.1055/a-0800-0113
|View full text |Cite
|
Sign up to set email alerts
|

Personal Radiation Protection and Corresponding Dosimetry in Interventional Radiology: An Overview and Future Developments

Abstract: Background The increasing number of minimally invasive fluoroscopy-guided interventions is likely to result in higher radiation exposure for interventional radiologists and medical staff. Not only the number of procedures but also the complexity of these procedures and therefore the exposure time as well are growing. There are various radiation protection means for protecting medical staff against scatter radiation. This article will provide an overview of the different protection devices, their efficacy in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 57 publications
0
18
0
3
Order By: Relevance
“…Various studies have shown that a significant dose reduction can be achieved by using the ceiling mounted leadscreen [20][21][22][23][24][25]. If the lead screen is used optimally, an eye lens dose reduction of up to 50-60% may occur [20,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that a significant dose reduction can be achieved by using the ceiling mounted leadscreen [20][21][22][23][24][25]. If the lead screen is used optimally, an eye lens dose reduction of up to 50-60% may occur [20,23].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that a significant dose reduction can be achieved by using the ceiling mounted leadscreen [20][21][22][23][24][25]. If the lead screen is used optimally, an eye lens dose reduction of up to 50-60% may occur [20,23]. Optimal usage here reflects the positioning of the lead screen close to the skin of het patient, preferably positioned over the patient [9,20,22,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Presently, with the increase in the number of examinations using the radiation, it is important for the medical workers to know the ways how they can shield themselves effectively. [25][26][27] One of the components that can contribute to the correct way of shielding the workers is a measure of knowledge about the radiation safety, which has a big influence on the correct actions and performance in the field of radiation safety. Within this context, Behzadmehr conducted a systematic review.…”
Section: Role Of Public Health In Radiation Safety Of the Medical Workersmentioning
confidence: 99%
“…The existence of PO4 & BO4 structural units, this consequence approaches from the structural issues connected with covalent links. In several fields, B2O3-P2O5 -Li2O -MoO3 glasses possess high applications because of their radiation shielding and good FT-IR transmission [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The object of this study is to assist you in the preparation of B2O3-P2O5 -Li2O -MoO3 glasses and investigating their optical and neutron shielding using Phy-X/PSD [34] properties.…”
Section: Introductionmentioning
confidence: 99%